Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/slct.201702083
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanoparticle‐Immobilized Porous Polyurethane Material for Quick and Efficient Heterogeneous Catalysis of Suzuki‐Miyaura Cross‐Coupling Reaction at Room Temperature

Abstract: Here we report, room temperature heterogeneous catalysis of the Suzuki‐Miyaura cross‐coupling reaction by a Pd0 nanoparticle‐immobilized porous organic polymer (TPU‐Pd), providing excellent yields (up to 99%) using low catalyst loading. High nitrogen‐ and oxygen‐donor content of triazine‐based porous polyurethane (TPU) makes it an efficient porous polymer for Pd‐immobilization and subsequent heterogeneous catalysis of C–C cross‐coupling reactions. X‐ray photoelectron spectroscopy of TPU‐Pd showed characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 60 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Along the same lines, 139,170 Dey et al reported triazinebased porous polyurethane for immobilization of Pd NPs. 171 However, unlike TP-POP and PC-POP, the triazine-based polymer contained mesopores with sizes between 2 and 20 nm which resulted in an exceptionally broad distribution of Pd NPs (5−20 nm). The authors claim a successful Suzuki− Miyaura cross-coupling reaction, but it is difficult to follow the structure−property relationships with such a catalyst.…”
Section: Mesoporous Polymersmentioning
confidence: 99%
“…Along the same lines, 139,170 Dey et al reported triazinebased porous polyurethane for immobilization of Pd NPs. 171 However, unlike TP-POP and PC-POP, the triazine-based polymer contained mesopores with sizes between 2 and 20 nm which resulted in an exceptionally broad distribution of Pd NPs (5−20 nm). The authors claim a successful Suzuki− Miyaura cross-coupling reaction, but it is difficult to follow the structure−property relationships with such a catalyst.…”
Section: Mesoporous Polymersmentioning
confidence: 99%
“…Porous organic framework materials (POPs), including metal organic framework (MOFs), covalent organic framework, and hydrogen-bonded organic framework, have been widely explored in gas storage, separation, biosensing, heterogeneous catalysis, and the medical field in the past decade due to their unique structure and performances. Porphyrin, as a popular organic chromophore, is widely distributed in human heme and plant chlorophyll. It plays important roles in photosynthesis of plants and oxygen transport in human blood .…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, immobilized systems are very attractive for the catalysis (reduction‐hydrogenation, oxidation, C‐C bond formation reactions etc.). Similar expressions can be said for materials or complexes containing palladium metal and the location of the palladium compounds is to particular importance in the catalyst chemistry . Likewise, the materials or complexes bearing palladium have been used for various purposes in photovoltaic studies …”
Section: Introductionmentioning
confidence: 90%